Development and validation of a method for precise dating of female puberty in laboratory rodents: The puberty ovarian maturation score (Pub-Score) - Francisco Gaytan; Concepción Morales; Silvia Leon; Violeta Heras; Alexia Barroso; Maria S. Avendaño; Maria J. Vazquez; Juan M. Castellano; Juan Roa; Manuel Tena-Sempere (NATURE PUBLISHING GROUP, 2022)
Puberty is a key developmental event whose primary regulatory mechanisms remain poorly understood. Precise dating of puberty is crucial for experimental (preclinical) studies on its complex neuroendocrine controlling networks. In female laboratory rodents, external signs of puberty, such as vaginal opening (VO) and epithelial cell cornification (i.e., first vaginal estrus, FE), are indirectly related to the maturational state of the ovary and first ovulation, which is the unequivocal marker of puberty. Whereas in rats, VO and FE are almost simultaneous with the first ovulation, these events are not so closely associated in mice. Moreover, external signs of puberty can be uncoupled with first ovulation in both species under certain experimental conditions. We propose herein the Pubertal Ovarian Maturation Score (Pub-score), as novel, reliable method to assess peripubertal ovarian maturation in rats and mice. This method is founded on histological evaluation of pre-pubertal ovarian maturation, based on antral follicle development, and the precise timing of first ovulation, by retrospective dating of maturational and regressive changes in corpora lutea. This approach allows exact timing of puberty within a time-window of at least two weeks after VO in both species, thus facilitating the identification and precise dating of advanced or delayed puberty under various experimental conditions.